Intracerebral Transplants and Memory Dysfunction: Circuitry Repair or Functional Level Setting? - Bruno Will; Christian Kelche; Jean-Christophe Cassel (Neural Plasticity)
Intracerebral grafting techniques of fetal neural cells have been used essentially with two main types of lesion paradigms, namely damage to long projection systems, in which the source and the target are clearly separate, and damage to neurons that are involved in local circuits within a small (sub)region of the brain. With the’first lesion paradigm, grafts placed homotopically (in the source) are not appropriate because their fibers grow poorly through the host parenchyma and fail to reach their normal target. To be successful, the grafts must be placed ectopically in the target region of the damaged projection systems, where generally they work as level-setting systems. Conversely, with the second paradigm, the grafts are supposed to compensate for a local loss of neurons and must be placed homotopically to induce functional effects that are based on the reconstruction of a point-to-point circuitry. By inserting a biological or artificial bridging-substrate between the source and the target of long projection systems, it might be possible to combine the positive effects of both homotopic and ectopic grafting by achieving both target reinnervation and normal control of the grafted neurons within the source area. These issues are illustrated and discussed in this review.